A Critical Review Philosophy of Psychology - Fatemeh Javadzadeh Shahshahani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
After the approval of the title of “Philosophy of Science in Psychology” as a two-credit course for undergraduate university students of psychology, several textbooks were developed with a similar title. The most recent textbook, by Dr. Khosro Bagheri was published by the Organization for Researching and Composing University Textbooks in the Humanities. Taking these two points into consideration, the current book is introduced and evaluated; however, its modification and completion in the next edition will certainly provide an opportunity for a unique textbook to be developed in philosophy of psychology. In the present study, after the introduction of different chapters of “Philosophy of Psychology Science”, the book is evaluated from several angles, including (the appearance, title, consistency with the approved course of this credit, appropriateness with the approved syllables of the relevant courses, and the appropriateness of books with similar books). The evaluation result indicate that the present book “Philosophy of Psychology Science” which is written by Khosro Bagheri, as a textbook of “Philosophy of Psychology Science”, has many advantages; however, it revision in the next edition in terms of name, volume, chapter numbers, title and content, is needed in order for it to be matched well with the developed topics for this course. Finally, one suggestion would be offered, improving the philosophy of psychology science course and some reasons for that.